Hubungan pola makan dengan resiko gastritis Pada mahasiswa yang menjalani sistem kbk - Sri - Hartati; Wasisto - Utomo; Jumaini - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to analize the relationship between diet with the risk of gastritis for competency-based curriculum system students. This study was a correlational study with cross sectional approach. The sampling technique was simple random sampling with 115 competency-based curriculum system students were selected based on inclusion criteria. Data were analyzed by using univariate analysis to determine the distribution of frequencies and bivariate analysis by using Chi-Square. The results showed that p value (0,004) < alpha (0,05). It meant that there was a relationship between diet and the risk of gastritis competency-based curriculum system students. Besed on this result, it suggest to students keep their health statis by maintaining a regular diet and prevent the causes that can stimulate to gastritis. Keywords: Competency-based curriculum system, Diet, Risk of gastritis